International price relationship between Malaysian stock exchange composite index with Dow Jones Industrial average, Hang Seng index and Nikkei 225 average index - Abdul Latif, Azlin; Ismail, Nor Hazila; Samsudin, Syamsyul (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2007)
This project paper is carried out with the criterion of providing readers better understanding in examining the linkages stock market by using the index in each selected country to represent the relationship towards Malaysia Stock Exchange (MSE). The objective of the study is to determine whether there are any relationships between Malaysia Stock Exchange Composite Index with Dow Jones Industrial Average, Nikkei 225 Average Index and Hang Seng Index. The daily data are collected from January 1995 to 2005 (10 years). Data collection will be analyzed and interpreted by using econometrics analysis. The data analysis in this study involved four steps which is stationarity test, ordinary least squares (OLS), diagnostic test and final model. The obtained result indicates that other markets such United States, Japan and Hong Kong markets are not highly influenced on Malaysia Stock Exchange